Novel aortic heart valve model parameterizing normal and pathological cases: Aortic stenosis and regurgitation - Iscan, Mehmet; Yesildirek, Aydin (SAGE PUBLICATIONS LTD, 2023)
In this paper, a novel heart valve model with parameters selections enabling to illustrate some physiological patterns such as healthy, aortic stenosis, and regurgitation has been shown. The motion of the elastic leaflet body is modeled by a nonlinear mass-spring-damper and coupled with a cardiovascular lumped parameter model. As a result, our model takes in to account a single continuous time-varying fluid resistance, the aortic flow rate, left ventricular and aortic pressures, and the leaflets' pose. This novel model is able to show the backflow, vortex and dicrotic notch phenomenon as approaching to the gold standard in physiological evaluation. The model also additionally presents reverse pressure effect on the aortic valve in the diastolic phase that is not observed in the recent literature. The physiological validation is performed by comparing two reference models and previously reported on physiological data. Nominal leaflet spring (a) and damping (c) parameters have been determined for the healthy valve (a = 0.1, c = 2), aortic stenosis (a = 0.005, c = 0.1), and aortic regurgitation (a = 0.001, c = 2). When compared to other studies, the left ventricular and aortic pressure, leaflets' opening-closing angles are generated in similar patterns. In addition, the reduction of the blood flow rate can now be observed in aortic regurgitation, which is not presented in the literature. In conclusion, a set of critical aortic valve conditions is parameterized by our novel model. The elastic structure of the leaflet model enabling us to demonstrate not only the vortex and dicrotic notch phenomenon but also the backflow and reverse pressure effect. Furthermore, it offers a generalized framework to realize extensive aortic valve conditions.
Keywords: Heart valves; aortic valve; aortic valvular stenosis; aorta regurgitation; DYNAMICS; PRESSURE; GRADIENT; DISEASE; Automation & Control Systems; Instruments & Instrumentation